THE EFFECT OF SELF CONTROL THROUGH GROUP COUNSELING ON STUDENTS’ AGGRESSIVE BEHAVIOR TENDENCY - Maisaroh, Dewi; Dharmayana, I Wayan; Afriyati, Vira (UNIB Press, 2016)
Abstract: This research aimed to describe the effect of self control through group counseling on students’ aggressive behavior tendency. The method quasi experimental method with one group pre-test post test design. The subject was 6 students class VIII at SMPN 12 Kota Bengkulu who had very high and high aggressive behavior tendency. The technique of collecting data was questionnaire. The result showed that the students’ aggressive behavior decreased after giving self control exercise through group counseling. It was showed by the result of difference test Z = -2,201 (p<0,05).